Identifying the localization and exploring a functional role for Gprc5c in the kidney. Issue 4 (5th January 2018) - Rajkumar, Premraj; Cha, Boyoung; Yin, Jianyi; Arend, Lois J.; Păunescu, Teodor G.; Hirabayashi, Yoshio; Donowitz, Mark; Pluznick, Jennifer L.
Abstract : The investigation of orphan GPCRs (GPRs) has the potential to uncover novel insights into whole animal physiology. In this study, our goal was to determine the renal localization of Gprc5c, a receptor that we previously reported to be highly expressed in murine whole kidney, and to examine physiologic parameters in Gprc5c knockout (KO) mice to gain insight into function. Gprc5c localized to the apical membrane of renal proximal tubules (PTs) in mice, rats, and humans. With the comparison of Gprc5c wild‐type (WT) and KO mice, we found that Gprc5c KO mice have altered acid‐base homeostasis. Specifically, Gprc5c KO mice have lower blood pH and higher urine pH compared with WT mice, with a reduced level of titratable acids in their urine. In an in vitro GPCR internalization assay, we observed that Gprc5c internalization (an index of activation) was triggered by alkaline extracellular pH. Furthermore, with the use of an in vitro BCECF assay, we observed that Gprc5c increases Na + /H + exchanger 3 (NHE3) activity at alkaline pH. We also find that the NHE3 activity is reduced in Gprc5c KO mice by 2 photon imaging in seminaphthorhodafluors (SNARF)‐4F‐loaded kidney sections. NHE3 is a primary contributor to apical transport of H + in the renal PT. Together, these data imply that Gprc5c modulates the renal contribution to systemic pH homeostasis, at least in part, by taking part in the regulation of NHE3.— Rajkumar, P., Cha, B., Yin, J., Arend, L. J., Paunescu, T. G., Hirabayashi, Y., Donowitz, M., Pluznick, J. L. Identifying the localization and exploring a functional role for Gprc5c in the kidney. FASEB J. 32, 2046–2059 (2018). www.fasebj.org